Peningkatan mutu pembelajaran melalui implementasi media pembelajaran berbasis lesson study - Sofyan Mahfudy; Kuriniawan Arizona (Jurnal Participative: Jurnal Pengabdian Pada Masyarakat, 2021)
Teacher professionalism plays an important role in education because it determines the quality of teaching and learning in the classroom. One aspect of teacher professionalism is the ability to design good learning and skills in using learning media to increase learning effectiveness. The existing phenomenon is that teachers are not optimal in designing lesson plans that utilize attractive and interesting learning media. Therefore, efforts are needed to improve the ability of teachers in designing good lesson plans by utilizing learning media. This community service aims to provide understanding and knowledge to teachers in utilizing the media as a learning tool and applying the principles of lesson study to the learning process. The service is carried out in two stages, namely training in the form of workshops and mentoring for model teachers. The results of the mentoring show the teacher's understanding of the importance of using learning media. In addition, teachers also have knowledge in designing learning with the principle of lesson study to be applied in the implementation of learning in the classroom.